2023
DOI: 10.1021/acsmaterialslett.2c01087
|View full text |Cite
|
Sign up to set email alerts
|

Selective Crystallization of a Highly Radiation-Resistant Isonicotinic Acid-Based Metal–Organic Framework as a Primary Actinide Waste Form

Abstract: Isonicotinic acid (INA), as a prototypical N,O-donor bifunctional ligand, has demonstrated its ability to differentiate Th 4+ from representative ions for products in spent nuclear fuels

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Utilizing Th-based multi-functional materials for monitoring and sequestrating more radioactive radionuclides represents a promising strategy to overcome the aforementioned challenge. As a subgroup of MOFs, Th-MOFs inherit the combinatorial benefits of high porosity, a large surface, and structural modularity, which offer the potential of capturing specific radionuclides in their voids. Moreover, integrating luminescent organic linkers in a framework matrix allows for the spatial distribution of the fluorophores, which eliminates aggregation-induced quenching (AIQ) and enhances the sensing efficacy via increasing the photoluminescence quantum yield. Indeed, actinide-based MOFs have stood out as a unique and efficient platform for capturing radionuclides, including 85 Kr, 99 Tc, 129/131 I, and 137 Cs in ionic or molecular forms. However, the sector of radionuclide sensing based on actinide MOFs is much less explored, despite the fact that they feature unique photoswitch properties such as photoluminescence, photochromism, and fluorochromism. , …”
Section: Introductionmentioning
confidence: 99%
“…Utilizing Th-based multi-functional materials for monitoring and sequestrating more radioactive radionuclides represents a promising strategy to overcome the aforementioned challenge. As a subgroup of MOFs, Th-MOFs inherit the combinatorial benefits of high porosity, a large surface, and structural modularity, which offer the potential of capturing specific radionuclides in their voids. Moreover, integrating luminescent organic linkers in a framework matrix allows for the spatial distribution of the fluorophores, which eliminates aggregation-induced quenching (AIQ) and enhances the sensing efficacy via increasing the photoluminescence quantum yield. Indeed, actinide-based MOFs have stood out as a unique and efficient platform for capturing radionuclides, including 85 Kr, 99 Tc, 129/131 I, and 137 Cs in ionic or molecular forms. However, the sector of radionuclide sensing based on actinide MOFs is much less explored, despite the fact that they feature unique photoswitch properties such as photoluminescence, photochromism, and fluorochromism. , …”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs), crystalline hybrid materials having the rigidity of inorganic and flexibility of organic materials, exhibited high potential in the extraction of metal ions including actinides. Since their invention, MOFs have been designed with task of performing a great variety of applications , thanks to their high surface area, porosity, structural tailorability, and ease of synthesis. Recently, Lillerud et al first reported synthesis of Zr 4+ containing a porous organic framework made of dicarboxylic acid termed as UiO-66.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this Perspective provides a conceptual framework that guides the design of innovative thorium-based materials and outlines potential solutions for addressing urgent needs in the nuclear energy and waste remediation ,, sectors from the lens of Zr- and U- chemistry.…”
Section: Introductionmentioning
confidence: 99%